Jojo's bizarre adventure. Part 1, Phantom blood - Araki, Hirohiko, 1960- (Shonen Jump advanced., 2015)
"Young Jonathan Joestar's life is forever changed when he meets his new adopted brother, Dio. For some reason, Dio has a smoldering grudge against him and derives pleasure from seeing him suffer. But every man has his limits, as Dio finds out. This is the beginning of a long and hateful relationship!"--